Ecocrítica y chamanismo en la poesía de Pablo Antonio Cuadra - White, Steven F. (Anales de Literatura Hispanoamericana, 2004)
This study uses an ecocritical focus to explore the shamanic voice that characterizes the literary speaker throughout the poetic works of Nicaraguan Pablo Antonio Cuadra (1912-2002), from Poemas nicaragüenses (1934) to El indio y el violín (2000).